Pengaruh Volume Kendaraan Terhadap Tingkat Kerusakan Jalan Pada Perkerasan Rigid di Kota Binjai - Fahri, Tengku Muhammad (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2023)
Highways are of a very petrified public interest to facilitate life, road damage that occurs in various regions today is a very complex problem and the losses suffered are very large, especially for road users, the volume of vehicles is proportional to the level of road damage.  Rigid pavement or rigid pavement is a type of road pavement that uses concrete as the main material of the pavement, is one type of road pavement used apart from bending pavement (asphalt). The purpose of this study is  to determine the effect of the number of vehicles on road damage on Rigid pavement in Binjai City which results  in heavy vehicles of 100 kend / day will increase the level of road damage by 10.1, the  volume of light vehicles and heavy vehicles has a percentage of 86%. The higher the volume of the vehicle, the greater the damage that occurs.